Nicotianamine Synthesis by OsNAS3 Is Important for Mitigating Iron Excess Stress in Rice - Aung, May Sann; Masuda, Hiroshi; Nozoye, Tomoko; Kobayashi, Takanori; Jeon, Jong-Seong; An, Gynheung; Nishizawa, Naoko K. (Frontiers in Plant Science, 2019)
Iron (Fe) toxicity in plants causes tissue damage and cellular homeostasis disorders, thereby affecting plant growth and development. Nicotianamine (NA) is a ubiquitous chelator of metal cations and is responsible for metal homeostasis. In rice, it is synthesized by three NA synthase (NAS) genes, of which the expression of OsNAS1 and OsNAS2 but not of OsNAS3 is strongly induced in response to Fe deficiency. Recently, we found that OsNAS3 expression is strongly induced with excess Fe in most rice tissues, particularly old leaves, suggesting that it may play a vital role under excess Fe conditions. However, how OsNAS3 participates a role in response to excess Fe in rice remains poorly understood. In this study, we clarified the physiological response of OsNAS3 expression to excess Fe and the role of NA synthesis in this condition. Promoter GUS analyses revealed that OsNAS3 was widely expressed in roots, especially in vascular bundle, epidermis, exodermis, stem, and old leaf tissues under Fe excess compared to control plants. NA and deoxymugineic acid (DMA; a type of phytosiderophore synthesized by Strategy II species) were present in both roots and shoots under Fe excess likewise under control conditions. In addition, OsNAS3 knockout plants were sensitive to excess Fe, exhibiting inferior growth, more severe leaf bronzing, and greater Fe accumulation than non-transformants with excess Fe. Moreover, the knockout plants accumulated more Fe in their leaves than non-transformants. We also observed that NA-overproducing rice was tolerant to excess Fe. Overall, these findings suggest that rice synthesizes NA with OsNAS3 under Fe excess in roots and shoots, and that NA and DMA within the plant body are important for mitigating excess Fe stress and alleviating other metal deficiencies in rice. This report will be important for the development of tolerant rice adapted to Fe-contaminated soils.